Aspectos morfológicos dos aparelhos reprodutores, maturação de ovários e avaliação do desenvolvimento de ninfas de Quesada gigas (Olivier, 1790) (Hemíptera: Cicadidae) em relação a diferentes hospedeiros - Andrade, Samuel de Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Quesada gigas (Olivier, 1790) (Hemiptera: Cicadidae) is a species of cicada widely distributed in the America continent, which the nymphs feed on xylem fluid. In addition to the native host, Q. gigas can also be found in coffee plants, being the immature stages considered pest in the coffee producer region of southern Minas Gerais state and Northeast of São Paulo state. The emergence of the large amount of Q. gigas adults is concentrated in the period between September and November, during which also happen mating and laying. The posture of Q. gigas eggs is endophytic type and is implemented inside dry branches, preferably at the the upper canopy of coffee plants. Despite, many biological aspects of Q. gigas are not yet determined, including processes related to reproduction, and those involved the interaction of the nymphs (stage causing damage), with their hosts. The main goal of the research was to determine morphology of the reproductive apparatus of Q. gigas, watching the maturation of ovaries, as well as assess nymphs development in relation to different host plants. The studies were conducted in the field of Experimental Station of Agricultural Research Company of Minas Gerais (EPAMIG) (20º57‟54.32‟‟S; 47º04‟16.07‟‟W) and in UNESP/FCAV laboratories. Through stereomicroscopic analysis and scanning electron microscopy we can observe the structures present in the Q. gigas female reproductive apparatus. It can be seen from the beginning of emergency 30/09/2013 adults, difference between immature and mature ovaries in females compared to the first and second collect period 10/14/2013 and 29/10/2013 respectively. The number of eggs per female found in the second collect 29/10/2013 varied 112-1017 averaging 428.2 ± 45.7 eggs/female. The female's ovipositor is characterized by apical teeth, pre-apical and dorsal. Eggs have elongated and cylindrical structure. The exochorion consists of tubers united by furrows and ...

Quesada gigas (Olivier, 1790) (Hemiptera: Cicadidae) é uma espécie de cigarra com ampla distribuição geográfica no continente americano, cujas ninfas se alimentam de fluidos do xilema. Além dos hospedeiros nativos, Q. gigas também pode ser encontrada em cafeeiros, sendo as fases imaturas consideradas praga na região cafeeira do Sul do Estado de Minas Gerais e Nordeste do Estado de São Paulo. A emergência da maior quantidade de adultos de Q. gigas está concentrada no período entre setembro e novembro, período em que também acontecem o acasalamento e a postura. A postura de Q. gigas é do tipo endofítica e é realizada no interior de ramos secos, preferencialmente na parte superior das plantas de café. Entretanto, muitos aspectos biológicos de Q. gigas ainda não estão determinados, dentre eles processos ligados à reprodução e aqueles envolvidos na interação das ninfas (fase causadora de danos) com seus hospedeiros. Sendo assim oobjetivo da pesquisa foi determinar aspectos morfológicos dos aparelhosreprodutores de Q. gigas, observando a maturação de ovários, bem como avaliar o desenvolvimento de ninfas dessa espécie em relação a diferentes plantas hospedeiras. Os estudos foram conduzidos na área da Estação Experimental da Empresa de Pesquisa Agropecuária de Minas Gerais (EPAMIG) (20º57‟54.32‟‟S; 47º04‟16.07‟‟O) e em laboratórios da UNESP/FCAV. Através de análise estereomicroscópica e de microscopia eletrônica de varredura pôde-se observar as estruturas presentes nos aparelhos reprodutores de Q. gigas. Pôde-se verificar a partir do início da emergência de adultos 30/09/2013, a diferença entre ovários imaturos e maduros nas fêmeas em relação ao primeiro e segundo período de coleta 14/10/2013 e 29/10/2013, respectivamente. O número de oócitos encontrados por fêmea na segunda coleta 29/10/2013 variou de 112 a 1.017 com média de 428,2±45,7 ovos/fêmea. O ovipositor da fêmea é ...
Keywords: Café - Doenças e pragas; Hemiptera; Inseto - Morfologia; Inseto - Reprodução; Agricultural pests